Immunization with nanovaccines containing mutated K-Ras peptides and imiquimod aggravates heterotopic pancreatic cancer induced in mice - Martínez-Pérez, Amparo; Diego-González, Lara; Vilanova, Manuel; Correia, Alexandra; Simón-Vázquez, Rosana; González-Fernández, África (Frontiers in Immunology, 2023)
Purpose: The growing incidence and lethality of pancreatic cancer urges the development of new therapeutic approaches. Anti-tumoral vaccines can potentiate the immune response against the tumor, targeting specific antigens expressed only on tumor cells. In this work, we designed new vaccines for pancreatic cancer, composed by chitosan nanocapsules (CS NCs) containing imiquimod (IMQ) as adjuvant, and targeting the K-Ras mutation G12V. Experimental design: We tested the immunogenicity of our vaccines in mice, carrying different combinations of K-Ras mutated peptides. Then, we analyzed their prophylactic and therapeutic efficacy in mice bearing heterotopic pancreatic cancer. Results: Unexpectedly, although good results were observed at short time points, the different combinations of our CS NCs vaccines seemed to potentiate tumor growth and reduce survival rate. We propose that this effect could be due to an inadequate immune response, partially because of the induction of a regulatory tolerogenic response. Conclusion: Our results call for caution in the use of some NCs containing IMQ in the immunotherapy against pancreatic cancer.